2022
DOI: 10.1186/s12916-022-02628-2
|View full text |Cite
|
Sign up to set email alerts
|

The presence and impact of multimorbidity clusters on adverse outcomes across the spectrum of kidney function

Abstract: Background Multimorbidity (the presence of two or more chronic conditions) is common amongst people with chronic kidney disease, but it is unclear which conditions cluster together and if this changes as kidney function declines. We explored which clusters of conditions are associated with different estimated glomerular filtration rates (eGFRs) and studied associations between these clusters and adverse outcomes. Methods Two population-based cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Recently, association between clusters of multimorbidity patterns within groups of CKD patients and adverse events has been investigated, nding adverse outcomes to be associated with patterns of multimorbidity including known patterns of diabetes and cardiovascular disease, and relatively unknown patterns of pain and depression (Sullivan et al, 2022). Our results support this, showing that there are multimorbidity patterns that should be identi ed at diagnosis of renal failure in order to triage secondary care females and males.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, association between clusters of multimorbidity patterns within groups of CKD patients and adverse events has been investigated, nding adverse outcomes to be associated with patterns of multimorbidity including known patterns of diabetes and cardiovascular disease, and relatively unknown patterns of pain and depression (Sullivan et al, 2022). Our results support this, showing that there are multimorbidity patterns that should be identi ed at diagnosis of renal failure in order to triage secondary care females and males.…”
Section: Discussionsupporting
confidence: 73%
“…In such analyses, a disease may belong to more than one pattern, and the use of higher-level categories may hinder the identification of individuals who could benefit from earlier and/or more targeted interventions. For instance, Sullivan et al 58 found that the composition of multimorbidity patterns varied significantly based on the level of kidney dysfunction assessed using the estimated glomerular filtration rate (eGFR), with cardiovascular conditions becoming increasingly prominent at lower eGFR levels. Therefore, careful consideration of accuracy and granularity when defining chronic conditions is important to maintain a balance between disease misclassification and loss of potentially critical information.…”
Section: Discussionmentioning
confidence: 99%
“…While older people had more multimorbidity burdens, younger patients with CKD were at a higher risk of death from multimorbidity (36, 37). Severe CKD (eGFR <30 ml/min/1.73m 2 ) with clusters of heart failure, peripheral vascular disease, atrial brillation, diabetes, chronic pain, and depression was signi cantly associated with all-cause mortality and major cardiovascular events (32).…”
Section: Discussionmentioning
confidence: 99%